Pengembangan Cerita Anak dengan Pendekatan Ekolinguistik Sebagai Pengungkap Kearifan Lokal untuk Pelestarian Bahasa Jawa dan Lingkungan di SD - Endang Kurniati (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2017)
disclosure of local wisdom for the preservation of Javanese language and the environment of elementary students. The research approach used is research and development. This research product in the form of teaching material of the story that suitable with learning requirement of Javanese elementary school in the form of discourse which use Javanese dialect where the student is, by utilizing cultural activity, vocabulary, traditional expression, and fairy tale which is local wisdom. This teaching material uses Javanese dialect language [a] which can be used in Banyumas, Tegal, Brebes, and Javanese dialect [כ] which can be used in Surakarta, Semarang, and Yogyakarta.